2017
DOI: 10.4085/1062-6050-51.6.05
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Measures for Quantifying the Incidence of Concussion in National Collegiate Athletic Association Sports

Abstract: Although men's wrestling had a higher concussion rate and risk, men's football had the largest average number of concussions per team and the largest percentage of teams with at least 1 concussion. The risk of concussion, average number of concussions per team, and percentage of teams with concussions may be more intuitive measures of incidence for decision makers. Calculating these additional measures is feasible within existing injury surveillance programs, and this method can be applied to other injury type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 23 publications
(26 reference statements)
0
70
2
Order By: Relevance
“…Athlete head impacts continue to attract significant media and research attention with sports such as soccer, football, ice hockey, lacrosse, and rugby displaying significant rates of head injury in American high school and collegiate athletes (Kerr et al, ; O'Connor et al, ). These impacts occur across a continuum of severity; from injuries resulting in unconsciousness and requiring the athlete to be assisted on the field, to contact with no immediate observable consequences, such as heading a soccer ball.…”
Section: Introductionmentioning
confidence: 99%
“…Athlete head impacts continue to attract significant media and research attention with sports such as soccer, football, ice hockey, lacrosse, and rugby displaying significant rates of head injury in American high school and collegiate athletes (Kerr et al, ; O'Connor et al, ). These impacts occur across a continuum of severity; from injuries resulting in unconsciousness and requiring the athlete to be assisted on the field, to contact with no immediate observable consequences, such as heading a soccer ball.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that athletes exhibit higher levels of sensation‐seeking, aggression, and competitiveness (Ahmadi, Besharat, Azizi, & Larijani, 2011; Potgieter & Bisschoff, 1990; Zuckerman, 1983) and therefore may be more susceptible to injury (e.g., Kerr et al., 2017; Thompson & Morris, 1994). As expected, high‐risk athletic status was associated with a history of concussion: three‐quarters of those identifying as high‐risk athletes reported at least one previous concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprising perhaps, the incidence of concussion is higher in high‐risk sports (i.e., those that present a greater risk for injury such as hockey, football, or gymnastics) compared to low‐risk sports (e.g., basketball, baseball, and tennis; Beachy & Rauh, 2014; Gessel, Fields, Collins, Dick, & Comstock, 2007; Kerr et al., 2017; Marar, McIlvain, Fields, & Comstock, 2012; Noble & Hesdorffer, 2013). Indeed, in sporting leagues that permit contact play, the incidence of concussion is 3.88 times higher than that of noncontact leagues (Emery et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during the 2014 and 2015 seasons, nearly half of the NCAA Football Bowl Subdivision (FBS) college teams (60/128) did not publicly report a single concussion. 124 125 Such a figure remains low, particularly considering the number of head impacts athletes suffer on a consistent basis. The simultaneous co-existence of a high number of head impacts and relatively low number of concussions reported may indicate that a high prevalence of LD/ADHD in the football athlete population masks the severity of head impacts, resulting in artificially low concussion rates.…”
Section: Ld/adhd Brain Injury and Causationmentioning
confidence: 99%